Perancangan Meja Kerja Ergonomis bagi Perajin Sulaman Berbasis Quality Function Deployment - Umi Fadilah; Putri Endah Suwarni; Mirandhi Pratiwi; Susanti Sundari (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research was prompted by the issues of musculoskeletal health problems and a decline in production quality among embroidery artisans at UMKM A, both of which were caused by un-ergonomic workstations. The study aimed to design a functional and ergonomic workbench by first identifying the artisans' needs and then translating them into technical product specifications. The research used the Quality Function Deployment (QFD) method, which combines qualitative and quantitative approaches. The findings revealed a negative gap between the artisans' perceptions and their expectations, with scores ranging from -3.067 to -2.467 across 30 indicators. This negative gap highlights a clear need for improvement. Based on the QFD analysis, which was processed into the House of Quality (HOQ) matrix, seven key areas for improvement were identified. These included: a height-adjustable workbench design with a total score of 45 (41.85%), empty space under the table for leg movement with a score of 18 (16.74%), a design that aligns with the artisans' preferences with a score of 18 (16.74%), flexible adjustments for the table's position with a score of 6 (5.58%), and dedicated slots or racks for storing embroidery tools with a score of 6 (5.58%). In conclusion, the QFD method proved effective in designing a workbench that meets the artisans' needs, with the ultimate goal of increasing productivity and reducing the risk of injury.